The Impact of Coarse Aggregate Parent Rock Types on the Freeze–Thaw Performance of Concrete: A Comparative Study - Shihua Zhou; Cai Wu; Jiazheng Li; Yan Shi; Yuanyi Wang; Mingxing Luo (Buildings)
Hydraulic engineering projects in high-altitude environments are subject to significant diurnal temperature variations, necessitating concrete with high freeze–thaw resistance. Aggregates play a crucial role in the freeze–thaw durability of concrete. However, the impact of different parent rock types on concrete’s freeze–thaw resistance remains underexplored. This study investigated the effect of five common coarse aggregate types—granite (Gr), tuff (Tu), sandstone (Sa), limestone (Li), and pebble (Pe)—on the freeze–thaw resistance of dam concrete subjected to freeze–thaw cycles. The relationship between the rock type’s properties and the degradation patterns of concrete with different aggregates under freeze–thaw conditions was analyzed. Additionally, the damage mechanisms at the paste–aggregate interface were explored using SEM-EDS, pore structure analysis, and nano-indentation, along with the characteristics of the hydration products in the transition zone. The results showed that the aggregate type significantly influences freeze–thaw resistance, with Gr performing best (Gr > Li > Pe > Tu > Sa), correlating with pore structure and pore spacing. Gr, due to its superior freeze–thaw resistance, was optimal for regions with stringent freeze–thaw conditions. Although the interface zone exhibited a lower elastic modulus and hardness compared to the paste region due to a lower total amount of hydration products, these differences did not substantially affect the freeze–thaw performance of the concrete. This study, contributing to the expansion of the existing knowledge base on the effects of aggregate types on freeze–thaw resistance, provided valuable engineering insights for the selection of coarse aggregates in hydraulic concrete applications in high-altitude regions.